CASE REPORT UTERINE TORSION IN A GOAT ACCOMPANIED BY DYSTOCIA MANAGED BY FETOTOMY: A CASE REPORT - Ratih, Ni Komang Sri; Rahmawati, Ni Putu Dewi; Pamungkas, Kivlan Satrio; Ekaputri, Tesalonika Rouli; Ramadhan, Muhammad Agie; Adistia, Rani; Laksmi, Desak Nyoman Dewi Indira; Pemayun, Tjok Gde Oka; Trilaksana, I Gusti Ngurah Bagus; Bebas, Wayan; Susari, Ni Nyoman Werdi; Sukernayasa, I Wayan; et al. (Buletin Veteriner Udayana, 2026)
Uterine torsion is a common form of dystocia in small ruminants, including goats, and can lead to failure of normal parturition. This condition is characterized by uterine twisting, which impedes the fetus's passage through the birth canal. The purpose of this paper is to describe the management of a case of uterine torsion in a goat that resulted in a fetotomy due to the fetus's excessive size. This case began with symptoms of labor difficulty (dystocia) and no labor progress. Examination revealed uterine torsion, which hindered the normal position of the fetus. Corrective measures were taken, but were unsuccessful in restoring the uterus to its optimal position. Furthermore, the excessive size of the fetus (fetal oversize) exacerbated the condition, making it impossible to perform a normal extraction. Therefore, a fetotomy was decided upon as an alternative to save the mother. The procedure was performed carefully to minimize trauma to the mother's reproductive tissues. The final results showed that the fetotomy was effective in managing this case and successfully saved the mother.